Assessing the "Quality of Democracy" in Turkey. Issue 3 (2nd July 2016) - D'Elia, Silvia
ABSTRACT: Turkey is a case of a Muslim-majority country that has known an experience of representative democracy almost uninterrupted since the Second World War. The historical passages that have characterized the path to democracy in Turkey have configured the current set of powers. The aim of this article is to explore how the democratization process in Turkey is relevant in procedural, substantive, and result terms. In the first part is undertaken a historical overview from the perspective of modernization and democratic consolidation carried out by Turkey, also on the basis of the ability to meet the requirements of the Copenhagen political criteria. The second part investigates eight dimensions in which democracy spreads its effects in order to assess the quality of democracy of Turkey.